Damage Assessment by Numerical Modeling of Sant'Agostino's Sanctuary in Offida During the Central Italy 2016–2017 Seismic Sequence - Giordano, Ersilia; Clementi, Francesco; Nespeca, Andrea; Lenci, Stefano (Frontiers in Built Environment, 2019)
The subject of this work is the Sant’Agostino Sanctuary in Offida (Italy); we investigated both the dynamic behavior and the seismic vulnerability of the complex, used nowadays in its parts as school building, oratory, and church. Offida is in central Italy; the village has been severely damaged by the last seismic events of 2016. The sanctuary was heavily damaged by the earthquake of 24 August 2016. We recurred to finite elements to estimate the vulnerability of the sanctuary and its dynamic response, considering masonry’s nonlinear behavior by means of proper constitutive assumptions. To estimate how the monastery bears the lateral loads related to the expected demands resulting from seismic actions (N2 method) using nonlinear static analysis (Pushover), we recurred to a homogenized material and smeared cracking and crushing constitutive law. As may be remarked by observing buildings that share the same features of the sanctuary and, moreover, by comparing seismic demand vs. capacity, the structure is prone to massive damage leading to collapse. The paper underlines how advanced numerical analysis grants fundamental data on how historical masonry buildings behave under seismic action, providing a method that may easily be implemented at historic monasteries in Europe.